PENILAIAN TAMAN KOTA BANDA ACEH BERDASARKAN KRITERIA RUANG PUBLIK RAMAH ANAK - Arafah, Yunita; Fauzullana, Fauzullana; Sabila, Farisa; Refiyanni, Meidia (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2025)
The Child Friendly City policy is part of the fulfilment of children's rights in a city, including the provision of parks as creative and recreational facilities for physical development. However, from research conducted by Wulandari et al. (2022) on the implementation of KLA policies in Banda Aceh City found that the facilities and infrastructure provided by the Banda Aceh City government in an effort to fulfil children's rights have a lot of quantity, but in terms of quality it is still far from feasible, including children's playgrounds with play facilities that are not maintained and not suitable for use. The purpose of this study is to determine visitor perceptions of public spaces in Banda Aceh City as child-friendly public spaces. Measurement of visitors' perceptions is carried out because in this case visitors are connoisseurs of public space. The research location is in three parks in Banda Aceh City which are active parks according to DLHK3 Banda Aceh, namely Tibang City Forest Park, Bustanussalatin Park, and Meuraxa Tourism Park. This research was conducted using quantitative methods and analysed using Likert scale scoring and weighting techniques. Data were obtained from primary survey results, namely observation. Based on the results, it is known that the park in Banda Aceh still cannot bu fully said to be a child-friendly public space, where there are still many indicators that are not in accordance with the criteria for child-friendly public space. Therefoe, additions and improvements of facilities are needed for the parks